On the measurement and use of equality weighted growth: Spanish Network of Development Studies Award for Young Researchers’ Winner 2016 - Mongongo, Pacifique D. (Iberoamerican Journal of Development Studies, 2016)
If developing economies keep growing between 4 and 8 %, their current GDP will double between 2025 and 2034. By 2030, they will have already reached incomes above all reasonable poverty thresholds. Does this predict the end of poverty by 2030? By correcting mean income from inequality and comparing its growth to that of the overall GDP, this paper analytically shows that it depends on how such new wealth will be shared. It confirms that it will be the case if growth patterns will be creating jobs and opportunities for the less-well off and hence pull up their revenues. Applying this to sub-Saharan Africa (SSA), empirical results underpin that since 2000 SSA meets such a shared prosperity pattern. However, although forecasted to last and eradicate poverty by 2030, this pattern is not robust to crisis periods because it seems that people with lower incomes bear most of the burdens of recession.
Keywords: economic growth; inequality; MDGs; SDGs; GINI coefficient